2022
DOI: 10.3389/fphar.2021.762362
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Nanomaterials for Autoimmune Diseases Therapy

Abstract: Cationic nanomaterials are defined as nanoscale structures smaller than 100 nm bearing positive charges. They have been investigated to apply to many aspects including clinical diagnosis, gene delivery, drug delivery, and tissue engineering for years. Recently, a novel concept has been made to use cationic nanomaterials as cell-free nucleic acid scavengers and inhibits the inflammatory responses in autoimmune diseases. Here, we highlighted different types of cationic materials which have the potential for auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 96 publications
0
9
0
Order By: Relevance
“…Recently, cationic nanomaterials have been investigated for inhibiting inflammatory responses in autoimmune disease with some potential in mouse models of SLE. 54 Similarly small molecule compounds such as K-7174 have shown to attenuate NPSLE manifestations in lupus-prone mice. 55 These again might hold promise for future treatments in NPSLE and SLE-TM.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Recently, cationic nanomaterials have been investigated for inhibiting inflammatory responses in autoimmune disease with some potential in mouse models of SLE. 54 Similarly small molecule compounds such as K-7174 have shown to attenuate NPSLE manifestations in lupus-prone mice. 55 These again might hold promise for future treatments in NPSLE and SLE-TM.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Although the current application is still in its infancy and relevant studies are comparatively limited, it has shown potential in murine models of SLE. We may also look forward to its upcoming use in the treatment of NPSLE ( Xie et al, 2021 ).…”
Section: Manuscript Formattingmentioning
confidence: 99%
“…Towards this end, current approaches include systemic administration of cfDNA‐scavenging cationic biomaterials, which, however, are associated with concerns over the toxicity caused by the nonspecific cationic biomaterials. [ 19–21 ]…”
Section: Introductionmentioning
confidence: 99%
“…Towards this end, current approaches include systemic administration of cfDNAscavenging cationic biomaterials, which, however, are associated with concerns over the toxicity caused by the nonspecific cationic biomaterials. [19][20][21] Lymph nodes (LNs) are secondary lymphoid tissues that orchestrate a wide range of immune responses and maintain immune homeostasis. [22,23] Clinical studies indicated that 82% of RA patients show symptoms of lymphadenomegaly (enlarged LNs), which is associated with RA severity and treatment responsiveness.…”
mentioning
confidence: 99%